Does Tennis Training Improve Attention? New Approach - Şaban Ünver; İzzet İslamoğlu; Tülin Atan; Metin Yılmaz; Hayati Arslan; Abdurrahim Kaplan; Emre Şimşek (MDPI AG, 2023)
This study aimed to examine the effect of a tennis training program on improving attention. Methods: A total of 40 tennis players from a Tennis Club, 20 in the experimental group (EG) and 20 in the control group (CG), participated in the study. The EG athletes received 40 serve balls from the trainer twice a week for nine weeks. The researcher applied the "d2 attention test" to the EG and CG before and after the nine-week period. Results: After comparing the pretest and posttest attention averages of the experimental group, there was a significant difference in the TN, TN-E, and CP mean scores (p < 0.001). In the comparison of the pretest and posttest attention averages of the CG, there was no significant difference in the TN, TN-E, and CP mean scores (p > 0.05). The comparison of the pretest attention averages of the EG and CG revealed no significant difference in the TN, TN-E, and CP mean scores (p > 0.05). The comparison of the posttest attention averages of the EG and CG revealed a significant difference in the mean scores of TN, TN-E, and CP (p < 0.05). There was a statistically significant difference between the posttest-pretest differences in the TN, TN-E, and CP values of the EG and CG (p < 0.05). Conclusions: The study concluded that tennis training aimed at developing attention improved the results in the attention test.